Analisis Korelasi Antara Implementasi Sanitasi Total Berbasis Masyarakat (STBM) Pilar 2 dan 3 dengan Tingkat Kejadian Diare di Desa Lagego, Kecamatan Burau, Kabupaten Luwu Timur - Hasta, Meisya; Hidayat, Hidayat; Sulasmi, Sulasmi; Haderiah, Haderiah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Diarrhea is having three or more bowel movements a day with the consistency of loose stools which may be accompanied by vomiting or bloody stools.This study aims to determine the relationship between the implementation of Community-Based Total Sanitation (STBM) Pillars 2 and 3 with the incidence of diarrhea in Lagego Village, Burau District, East Luwu Regency. This type of research is analytic observational with a cross-sectional approach, that is going directly to the field using a questionnaire to the causal relationship between the two variables on an observational basis. The Result of this study indicate that 56 respondents have not implemented STBM pillar 2 and 30 respondents have implementes STBM pillar 2. As for the implementation of STBM pillar 3, there are 11 respondents who have not implemented STBM pillar 3 and 47 respondents who have implemented STBM pillar 3. The results of the analysis show that there is a relationship between the application of community-based total sanitation (STBM) pillar 2 with the incidence of diarrhea (p=0.000<0.05) and pillar 3 with the incidence of diarrhea (p=0.001<0.05). This is because the community still considers the behavior of washing hands with soap and the management of household food drinking water not included in things that are very important to do. Marry people especially those in the research locations have not implemented the STBM Pillars 2 and 3, so there are still many people who suffer from diarrhea. So that the community is advised to be able to apply STBM Pillar 2 (washing hands with soap) and Pillar 3 (management of household food drinking water) programs to avoid the occurence of diarrheal diseases. Keywords : Community Based Total Sanitation, Pillars 3 and 3 STBM, Diarrhar